HUKUM MENIKAHI WANITA HAMIL KARENA ZINA DAN KEDUDUKAN ANAKNYA - Ali Mohtarom (Fakultas Agama Islam Universitas Yudharta Pasuruan, 2020)
Free promiscuity between young and young people often brings things that are not desired, namely pregnancy before marriage. Pregnancy before marriage becomes a problem that requires a solution, because it brings anxiety in the community, especially parents, teachers and community leaders. Judging from the sociological, because they feel ashamed, the parents who happen to have their daughter pregnant out of wedlock try so that if their grandchildren are born there is a father. For that they try to marry off a man, be it a man who is impregnated or not. Therefore in this article the author will examine the opinions of the scholars and will examine the extent of the relevance of their opinions for now. Among them are, whether or not aqad of marriage is carried out in the condition of the pregnant woman, whether they may gather as befitting a husband and wife in a legal marriage, and what is the status of their children. So that the answers obtained as follows: a marriage between a man and a woman who impregnated himself, they may have intercourse like husband and wife. And it is also legal marriage between man and woman even though not the one who impregnates, but is not allowed to have sex like husband and wife until the woman gives birth. Whereas the status of his son only breathed to the mother not to the father (the man who impregnated him).